2011
DOI: 10.1016/j.psychres.2011.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of maltreatment and traumatic experiences in childhood and adolescence among predominantly African American, socially disadvantaged, hospitalized, first-episode psychosis patients

Abstract: Associations among maltreatment and traumatic experiences in childhood and adolescence, later substance use, and subsequent mental health outcomes for individuals with schizophrenia-spectrum disorders have been initially explored in previous studies; however, research on these factors in socially disadvantaged patients with first-episode psychosis is unavailable. This exploratory, correlational analysis examined associations between maltreatment and trauma-related variables (e.g., traumatic experiences, parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 58 publications
4
57
1
Order By: Relevance
“…Similarly, Bendall et al (2013b) reported that EP patients exposed to childhood sexual abuse had more severe hallucinations and delusions, and Wang and colleagues (2013) found CT was significantly correlated with hallucinations (r = 0.174, P = 0.049) in EP patients but not patients with chronic psychosis. Finally, a study by Ramsay et al (2011) found correlations between childhood emotional abuse and neglect and positive and negative psychotic symptoms, respectively, in disadvantaged, African-American EP inpatients.…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, Bendall et al (2013b) reported that EP patients exposed to childhood sexual abuse had more severe hallucinations and delusions, and Wang and colleagues (2013) found CT was significantly correlated with hallucinations (r = 0.174, P = 0.049) in EP patients but not patients with chronic psychosis. Finally, a study by Ramsay et al (2011) found correlations between childhood emotional abuse and neglect and positive and negative psychotic symptoms, respectively, in disadvantaged, African-American EP inpatients.…”
Section: Introductionmentioning
confidence: 93%
“…In a first pilot study (Compton et al, 2004) with 18 first episode psychosis patients, they described preliminary evidence of a more frequent childhood abuse among patients with comorbid cannabis dependence (n ¼ 8) than among those without it (n ¼ 10). In a subsequent analysis (Ramsay et al, 2011) of 61 first episode psychosis patients, the authors reported a significant bivariate association between emotional abuse in childhood and current positive symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…We have found only one clinical study (Compton et al, 2004), which was subsequently expanded (Ramsay et al, 2011), addressing the relationship between childhood trauma, cannabis use and psychosis development. According to the authors, they arrived at provisional results, not at strong conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations